6.0k views
5 votes
2(w+2) + w = 3( w -1 +6)

solve for w

User Igorsvee
by
7.1k points

1 Answer

1 vote

To solve for w in the equation 2(w+2) + w = 3(w-1+6), you'll need to simplify and isolate w step by step:

First, distribute the numbers outside the parentheses:

2w + 4 + w = 3w - 3 + 18

Combine like terms on both sides of the equation:

2w + w + 4 = 3w + 15

Next, combine the w terms on the left side of the equation:

3w + 4 = 3w + 15

Now, subtract 3w from both sides of the equation to isolate the constant term on the left side:

4 = 15

At this point, you'll notice that the variable w has canceled out on both sides of the equation, and you're left with 4 = 15. However, this is not a valid equation because 4 and 15 are not equal.

Therefore, there is no solution for w in this equation. The original equation is inconsistent and has no valid solution for w.

User Amichaud
by
7.1k points